Dynamic planning for navigation routes in unknown environments (2022)
Self-driving robots have to fulfill many different operations, as the coordination of mechanics in the robot (e.g., traction of motors, camera movement, actuator arms), and the actual movement of the robots --that is, driving to the places they need to reach. This task is the outmust importance for exploration robots, which must drive around exploring an area in an unknown terrain. As the area to drive is unknown, planning a specific route and driving plan is challenging, given that the chosen plan could be inappropriate for the given terrain, or even may find a mission with varying environments, which may not be appropriate for a given plan.